Entropy‐Maximized Synthesis of Multimetallic Nanoparticle Catalysts via a Ultrasonication‐Assisted Wet Chemistry Method under Ambient Conditions. Issue 7 (25th February 2019) - Liu, Miaomiao; Zhang, Zihao; Okejiri, Francis; Yang, Shize; Zhou, Shenghu; Dai, Sheng
Abstract: A facile ultrasonication‐assisted wet chemistry method for preparing multicomponent alloy nanoparticles (NPs) including high‐entropy alloys (HEAs) is reported. PtAuPdRhRu alloy (HEA), quaternary PtAuPdRh alloy, and ternary PtAuPd alloy NPs are produced with ≈3 nm in diameter. Taking advantage of the acoustic cavitation phenomenon in ultrasonication process, noble metal precursors could be co‐reduced by chemical reductants and transform to alloy structures under operation at room conditions. The instantaneous massive energy (≈5000 °C, 2000 atm) occurring in momentary timespans (≤10 −9 s) contributes to the formation of multimetallic mixed nanomaterials driven by entropy maximization. Owing to strong synergistic effects, the catalysts with the HEA NPs supported on carbons exhibit prominent electrocatalytic activities for hydrogen evolution reaction. Abstract : Taking advantage of the acoustic cavitation phenomenon in ultrasonic irraditions process, an ultrasonication‐assisted wet chemistry method is designed to alloy multimetallic elements in nanoscales. Quinary PtAuPdRhRu (high‐entropy alloy (HEA)), quaternary PtAuPdRh, and ternary PtAuPd nanoparticles are synthesized with diameters of ≈3 nm and supported on carbon in one step. The as‐synthesized HEA materials present excellent electrocatalytic performance for alkaline HER.